Effects of ionic composition on growth and survival of white shrimp Litopenaeus vannamei culture at low-salinity well water - Valenzuela-Madrigal,Ismael E (Universidad de Valparaíso. Facultad de Ciencias del Mar, 2017)
The culture of white shrimp Litopenaeus vannamei in low salinity waters (1.2 ± 0.5 g L-1) presents challenges, the deviation of the ionic composition of water is known that influences the overall condition of the cultured organisms. The effect of water of low salinity with different ion content on the growth and survival of shrimp was determined. First, water was extracted from 4 wells with a depth of 5 to 7 m, located in Sinaloa River Basin in Guasave, Mexico at: (T1) 25.43°N, 108.44°W; (T2) 25.48°N, 108.37°W; (T3) 25.60°N, 108.40°W and (T4) 25.64°N, 108.51°W and were selected on base the different ionic water composition. The experimental design was 4 independent treatments with 3 replicate. Shrimp were grown at sea water (Tm= 34 ± 1.4 g L-1) used as a control. Shrimps grown in Tm and T1 had averaged weight (over 12 ± 0.61 g) and survival rates (78%), with statistical differences to others low salinity water treatments. The condition factor obtained with low-salinity water (T1= 0.654) was like that recorded for Tm (0.670), where ionic ratios (Na/K and Mg/K) were similar to that of seawater. This observation strongly suggests that the ratios of the major ions (Na+, K+, Mg2+ and Ca2+) play a relevant role for development of organisms under cultivation. Shrimp cultured in water of low salinity with an ionic ratio similar to that of sea water were organisms with the best development under cultivation, therefore indicating that the proportion of major ions were important for shrimp.